Perhitungan Penyusunan Anggaran Keuangan Pada Produk Tempe Malang Anugrah - Indah Puji Lestari; Widiya Puji Astutik; Shobikin (Jurnal Hilirisasi Pengabdian Masyarakat, 2024)
Tempeh is a familiar food for Indonesian people. This food is very rich in nutrients, especially protein. Tempeh is a food that is no longer foreign to the Indonesian people. This food is rich in nutritional value, especially protein, besides being cheaper than animal protein sources, its taste is also very popular, besides being a side dish for meals, now tempeh is also developed into a snack. Indonesia is the largest tempeh producer in the world and the largest soybean market in Asia. The main purpose of this article is to find out the calculation plan for compiling a financial budget for processing soybeans into ready-to-sell tempeh.